(untitled) (University Arena, 2025)
Background. People may see the norms and rules as social constructs made to facilitate the cooperation between individuals. In this framework, the World Anti-Doping Agency has the role of ensuring a good function of the rules, including those which regulate the use of substances to enhance physical abilities. The difficulty consists in detaching the cases of doping from those which allow the administration of prohibited substances under the justification of therapeutic needs. Some athletes and coaches perceive the Therapeutic Use Exemptions as legal doping, a comparison which is the basis of the requirement to reduce the permissivity in using treatments during competitions for those who have certain medical problems. Objectives. The purpose of this study is to show that the tightening of the rules for those athletes who have medical problems is not desirable. Moreover, the research emphasizes that a reconsideration of prohibited substances is necessary, encouraging a greater permissivity in using them. Methods. Two methods are used to argue this claim: the first one, based on bibliographic research, will show that the interdiction of some substances has not a stable foundation, denouncing, at the same time, an arbitrary character; the second method will show that the equality principle and the respect for other competitors are not infringed by the athletes who are using prohibited substances for medical purposes. Conclusion. The research will lead to the conclusion that the possession of therapeutic use exemptions is not morally problematic. Moreover, it will emphasize the reasons why the World Anti-Doping Agency should not punish the athletes who accidentally break the anti-doping rules.